COMPARATIVE STUDY OF INGUINAL HERNIA MESH REPAIR WITH CONVENTIONAL PROLENE VERSUS TITANIUM SKIN STAPLES FOR FIXATION - Dr. Venkatesh, Dr. Ramesh C Sagar, Dr. Asif, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Inguinal hernia is one of the most common general surgical procedures performed worldwide. TheLichtenstein tension-free mesh repair is the current standard. However, the traditional method usingpolypropylene sutures for mesh attachment tends to take longer